مساهمة في دراسة كفاءة الخصوبة وبعض الصفات الحيوية عند جمبري النمر الأخضر Penaeus semisulcatus de Haan, 1844 في شاطئ جبلة - صقر فائز; زيني أديب; الحاطوم باسل (Latakia University Journal -Biological Sciences Series, 2019)
تناول هذا البحث لأول مرة دراسة كفاءة الخصوبة عند جمبري النمر الأخضر ( Green tiger Prawn) Penaeus semisulcatus في مياهنا الإقليمية كمقدمة لتربيته واستزراعه. نفذت هذه الدراسة في الفترة الممتدة من أيار 2008 وحتى حزيران 2009 في أربعة مواقع من شاطئ مدينة جبلة وهي: بستان الباشا, مصب نهر الرميلة, مصب مياه الصرف الصحي, ميناء الصيد. جمعت العينات بمعدل مرتين في الشهر من المنطقة الشاطئية وتحت الشاطئية من عمق (10 – 60 m). بلغ مجموع عدد عينات الأفراد التي جمعت 228 فرداً منها 129 أنثى و 99 ذكر وبنسبة %57 - %43 على التتالي, إذ تراوحت أطوال الإناث بين 7.5 – 23.1cm وسيطرة المجموعة ذات الأطوال حوالي 15 cm, وتراوحت أطوال الذكور بين 7.4 – 18.1 cm. وبسيطرة المجموعة ذات الأطوال حوالي 13 cm, وبلغ الحجم عند أول نضج جنسي 13.4cm للطول الكلي. أظهرت هذه الدراسة أن الإباضة تحدث خلال الفترة الممتدة بين شهر آذار وشهر تشرين الأول وبمعدل أعلى خلال شهر أيار. بلغت كفاءة الخصوبة عند إناث النوع P.Semisulcatus بين 78350 – 1315200 بيضة, وتراوحت أقطارالبيوض بين 0.26 – 0.31 mm. The research is a pioneering study of Reproductive Performance of Prawn Penaeus semisulcatus in our regional waters, which may serve as an introduction to its breeding and culture. This research was conducted in the period May 2008 - June 2009, at the following four regions on the coast of Jableh: Boustan ALbasha , estuary of ALrmayleh river, estuary of sewage flowing, and fishing port . Bimonthly samples were collected from littoral and sub littoral areas of 10-60 m deep. The total number of samples collected are 228 Individual: 129 females and 99 males and Proportion of 57% and 43% respectively. The sizes of the females varied between 7.5 cm to 23.1cm with high abundance of size group 15 cm, and the sizes of males ranged between 7.4-18.1 cm with dominance of length groups 13 cm . and Size at first sexual maturity was found to be 13.4 cm (total length). This study has shown that spawning takes place from March to October, with higher occurrence during May. fecundity of female P. semisulcatus ranged between 78350 – 1315200 eggs and Egg Size ranged between 0.26 – 0.31 mm.